Genetic diversity in three populations of Physalis peruviana using fractionation and electrophoretic patterns of seed storage protein - Bonilla, Henry (2019)
The genetic diversity of three populations designated as ecotypes of golden berry (Physalis peruaviana) is studied using protein quantification and polymorphism of seed storage proteins (SSPs) by denaturating polyacrylamide gel electrophoresis (SDS-PAGE). As well, biochemical characteristics of seed proteins were identified. The populations were from San Pablo province (Agroandino ecotype), Celendín province (Celendino ecotype) and Cajabamba province (Cajabamba ecotype), all from Cajamarca Department. There was not difference among the three populations based on protein quantification. Globulins (82.4%) were the majority fraction followed for albumins (13.9%), glutelins (3.7%) and prolamins (0.7%). Only albumins showed polymorphism, showing 21 proteins between ~6.5 to ~45 kDa and three different electrophoretic profiles, which were share among the three populations. Legumins and vicilins were identified in globulin fraction. Glutelins showed proteins of same molecular weight (MW) to legumins; and prolamins only a band of low MW. San Pablo province population (Agroandino ecotype) was completely uniform, while Cajabamba population showed higher genetic diversity followed by Celendin population. Our results shows that, based on seed proteins analyses is not possible to distinguish the three populations designated as Agroandino, Cajabamba and Celendino ecotypes.